2019
DOI: 10.5812/mejrh.91953
|View full text |Cite
|
Sign up to set email alerts
|

The Prevalence of Depression, Anxiety, and Stress and Their Association with Vitamin D and Estrogen Levels in Postmenopausal Women in Semnan

Abstract: Background: Depression, stress, and anxiety are of the most prevalent psychological disorders among postmenopausal women. Inadequate evidence is available on the association between vitamin D and estrogen with depression, anxiety, and stress in this group. Objectives:The objective of this study was to determine the prevalence of depression, anxiety, and stress and their association with vitamin D and estrogen levels in postmenopausal women in Semnan. Methods: The present analytical cross-sectional study was ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 44 publications
0
5
0
Order By: Relevance
“…Poomalar and Arounassalame 23 found the prevalence of anxious mood as 67.2% and 78.8%, respectively. Study by Nobahar et al 24 reported that among 120 postmenopausal women, anxiety levels were mild (46.7%), moderate (50.8%), and severe (2.5%); additionally, 79.2% had lower stress and 20.8% had greater stress.…”
Section: Anxietymentioning
confidence: 98%
“…Poomalar and Arounassalame 23 found the prevalence of anxious mood as 67.2% and 78.8%, respectively. Study by Nobahar et al 24 reported that among 120 postmenopausal women, anxiety levels were mild (46.7%), moderate (50.8%), and severe (2.5%); additionally, 79.2% had lower stress and 20.8% had greater stress.…”
Section: Anxietymentioning
confidence: 98%
“…Several observational studies have found that the transition to menopause is a period of increased risk of depression in women. 10,11,12 The results of research conducted by Zang et al (2016) note that there is a difference in age ranges between menopausal women who are depressed and who are not depressed. Length of education, chronic illness, and marital status are not associated with the incidence of depression in menopausal women.…”
Section: Incidence Of Depression In Menopausal Womenmentioning
confidence: 99%
“…Menopause represents a significant transitional phase in a woman's life, marked by both physical and emotional changes that can profoundly impact well-being. Among the various challenges faced during this period, depression and anxiety emerge as prevalent psychological concerns affecting menopausal women [1], [2]. The ramifications of these mental health issues extend beyond the individual, influencing overall quality of life, social interactions, productivity, and self-esteem.…”
Section: Introductionmentioning
confidence: 99%
“…Recognizing the prevalence and identifying risk factors associated with depression and anxiety in menopausal women in Iraq is crucial [1], [3]. Depression and anxiety, as highlighted in previous research [2], emerge as prevalent challenges during menopause, impacting various facets of women's lives. The ramifications of these mental health issues extend beyond the individual, influencing overall quality of life, social interactions, productivity, and self-esteem.…”
Section: Introductionmentioning
confidence: 99%